1988
DOI: 10.1071/zo9880217
|View full text |Cite
|
Sign up to set email alerts
|

Milk Consumption and Energetics of Growth in Pouch Young of the Tammar Wallaby, Macropus-Eugenii

Abstract: Milk consumption rates of young tammar wallabies, Macropus eugenii, were measured during the first 32 weeks of lactation by means of 22*Na turnover. Milk consumption rates were low during the first 18 weeks or so of lactation, rising from 1.2 to 9.0 ml d-'. Milk consumption rose to 43 ml d-' at 30 weeks post-partum. Changes in milk consumption were paralleled by increases in the size of mammary glands and weight gain by the sucklings. The mass gain for each millilitre of milk consumed (crude growth efficiency)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 4 publications
6
29
0
Order By: Relevance
“…These data are consistent with studies on Red deer [13], [14], Rhesus Macaques [15], [16], humans [36], [37] and the Trivers-Willard Model [5] that provides support for a mechanism by which wallabies with greater investment ability can allocate resources in favour of sons [21]. Lactation quantity and composition in macropods follows an endogenous maternal program independent of the pouch young sucking stimulus [26], [27] or the size of current pouch young when cross-fostered [38]. Therefore investment ability must depend on a pre-partum measure of condition [21].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These data are consistent with studies on Red deer [13], [14], Rhesus Macaques [15], [16], humans [36], [37] and the Trivers-Willard Model [5] that provides support for a mechanism by which wallabies with greater investment ability can allocate resources in favour of sons [21]. Lactation quantity and composition in macropods follows an endogenous maternal program independent of the pouch young sucking stimulus [26], [27] or the size of current pouch young when cross-fostered [38]. Therefore investment ability must depend on a pre-partum measure of condition [21].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore investment ability must depend on a pre-partum measure of condition [21]. Green et al [26] found that the conversion of protein and milk energy to body materials in tammar wallabies is intermediate compared with other mammals, suggesting that slow growth rates in the early stages of development may be due to restricted milk production by mothers. Mothers investing in sons are generally in a condition when the lactation program is set, that is indicative of high investment capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, two females in the natural forage treatment carried very small pouch-young (< 3 g) by the end of the experiment, but these young were each less than 20 days old and would have had a negligible impact on the mother's food requirements (see Green et al 1988) and were therefore unlikely to have affected digestive tract morphology.…”
Section: Discussionmentioning
confidence: 99%
“…California sea lion (Zalophus californianus Lesson) pups exhibited a similar decrease in energy available for growth between their first and second months of life, likely for similar reasons . In contrast, some species showed an increase in the proportion of energy available for growth with age (Green et al 1988;Merchant et al 1996; table 2). If the current study had extended to the period after pups completed molting, when pups are larger and have an adult coat, pups might have allocated more energy toward growth/storage, as seen in other species (Merchant et al 1996;Donohue et al 2002).…”
Section: Energy Budgets and Fmrmentioning
confidence: 99%